Compact multiservice monopole antenna for tablet devices. Issue 8 (3rd August 2018) - Subbaraj, Sangeetha; Kanagasabai, Malathi; Alsath, Mohammed Gulam Nabi; Ganesan, Geetha; Panneer Selvam, Yogeshwari; Kingsly, Saffrine
ABSTRACT: In this manuscript, a novel uniplanar monopole antenna for Tablet computer application is proposed. Multiband resonance is obtained by introducing multiple radiating branches and meandered stubs connected to the main monopole. Further, the impedance bandwidth of the operating bands is enhanced by introducing coupled parasitic stubs in the ground plane. The antenna has impedance bandwidth of 20 MHz (0.45–0.47 GHz), 270 MHz (0.69–0.96 GHz), 2370 MHz (1.43–3.8 GHz), 1600 MHz (4.9–6.5 GHz) for LTE 450/700/2300/2500 MHz, GPS, WLAN, Bluetooth applications, WiMAX and Wi-Fi applications. The size reduction of the proposed antenna is 60% compared to existing antenna solutions for tablet devices. The percentage bandwidth of the antenna is 4.35/34.2/90.6/23.2% for the four operating bands, respectively. Furthermore, the obtained gain of the antenna is greater than 1.8 dBi with peak gain of 5.65 dBi, and the efficiency is greater than 75%. The proposed antenna is tested on the mock-up system consisting of large ground plane of dimension 200 × 150 mm. The antenna is fabricated, and the measured results are compared with simulated results. The SAR is computed and found to be less than 1.6 W/Kg.